DAMPAK PERPANJANGAN RELAKSASI KREDIT TERHADAP LIKUIDITAS PERBANKAN SAAT PANDEMI COVID-19 - Daffa At Thariq; Pangestuty, Farah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research aims to analyze and compare liquidity in banks before the policy of extending credit relaxation and after the extension of credit relaxation during the pandemic in Indonesia. The ratio used as data is the current ratio from 2020 to 2021 to see how the state of banking liquidity is during the COVID-19 pandemic. The research sample used is several bank financial statements classified as BUKU 2, 3, and 4 banks in 2020 and 2021. The data analysis technique used in this study is the Paired Samples T Test because the data is normally distributed. The results showed that there was no significant difference in the liquidity of BUKU 2, 3, and 4 banks during the pandemic between before the extension of credit relaxation and after the extension of credit relaxation.